Lessons Drawn: Essays on the Pedagogy of Comics and Graphic Novels, David Seelow (2019). Issue 1 (1st July 2020) - Sinclair, Megan
Lessons Drawn: Essays on the Pedagogy of Comics and Graphic Novels, David Seelow (2019)Jefferson, MO: MacFarland, 186 pp., ISBN 978-1-47667-158-1, p/bk, £43.50